A direct reliability-based design method for tunnel support using the performance measure approach with line search. (March 2019) - Fang, Yanbing; Su, Yonghua; Su, Ya; Li, Shuai
Abstract: The performance measure approach (PMA) is used to address reliability constraints, and line search is employed since the reliability-based design (RBD) problem is translated into the solution to nonlinear equations. This RBD method is proposed for geotechnical engineering such as tunnelling, which is able to find design parameters automatically and directly with no trial-and-error process. Parametric analysis of RBD of support pressure suggests a conservative combination for tunnel support in weak rock. Furthermore, investigation of in situ stress reveals a drawback in the application of RBD, and the proposed RBD method can be helpful to detect the extreme value.